Manicheizmai ir Czesławas Miłoszas: moralinės vaizduotės tyrimas = Manichaeism and Czesław Miłosz : A Study of Moral Imagination - Mažeikis, Gintautas (Religija ir kultūra, 2016)
[full article and abstract in Lithuanian; abstract in English]This paper analyzes the stages and diversity of Manichaeism from the point of view of moral imagination and the history of ideas. Any form of Manichaeism considers evil as an autonomous or independent and essential power. From the view point of history of moral imagination, the paper separates several forms of Manichaeism. There is (1) Early Medieval Manichaeism, which is interpreted mostly by historians of religion. According to Hegel’s Philosophy of Religion, Christianity overcame the claims of the Gnostics and Manicheans, the opposing of material (natural) and spiritual (heaven) by proposing the Human Divine Jesus. However, this victory did not help to create and develop the theory of equal oppositions between heaven and earth and to legitimize the disequilibrium and the triggers of the one. (2) Late Medieval and Renaissance Manichaeans (Bogomils, Cathars, representatives of the poetry of Dolce Stil Nuovo and even the poetry of Courtly Love, Dante) believe in a selfish evil that possesses a poetic-demonic character and was represented by the philosophy of love. Renaissance Manichaeism emphasized the various emotionalities and was sometimes presented as a daemonic or divine or Satanist power. Monotheistic demonism became an expression of independent individual creativity, which was legitimized using new concepts of emotions, even in alienated and mystified forms. At the same time, (3) some texts of occult philosophy (authored by Heinrich Cornelius Agrippa, Paracelsus) related the imagination with demonic power. Some states of imagination were equated with the source of evil and the conditions of origin of the succubae and incubi. However, all four elements - rationality, material substance, emotion, and imagination - were not presented as oppositions of competent equilibrium but as the state of the fall, and they did not acquire a subjective developed character but existed only in an abstract demonic form. All parts of the imagined evil possess a subjective character in the poetry of the 17th-18th centuries, starting with John Milton’s Paradise Lost and George Byron’s Cain. This paper emphasizes the importance of the development of the characters of negative antagonists as a condition for presenting a protagonist and pays special attention to the development of Manichaeism in the books of Mikhail Bulgakov, Simone Weil and Czesław Milosz. Bulgakov followed the ideas of Renaissance thinker Grigory Skovoroda but, in his novel Master and Margarita, presented the situation where the evil is the state of Being and the good is the absence of evil. The same situation of marginalization of the good was presented by writers Ilya Ilf and Evgevy Petrov in their famous novels The Twelve Chairs and The Golden Ass. Weil presented a very classical theory of Manichaeism as a reaction to the tragic events of the 20th century and updated many of Cathars’ claims. Whereas in the paper, the main focus is paid to Miłosz’s The Land of Ulro (Ziemia Ulro). Miłosz updated many visions of William Blake, Emanuel Swedenborg, Oscar Milosz, Fyodor Dostoyevsky, and Adam Mickiewicz. The paper analyzes contemporary theoretical approaches to the Manichaeism from the viewpoint of Leonidas Donskis and Vytautas Kavolis in order to explain the theoretical possibilities for considering the problematic of moral imagination. The author of this paper distinguishes between evil and villainy. Evil is the moral source or an objectivity, and villainy is the state of the reason. Villainy is associated with Hegel’s "Cunning of Reason" (List der Vernunft). Cunning or artfulness is an essential characteristic of any form of villainy but could be used for the aims of goodness or evil. This analysis shows that Miłosz presented both possibilities in his critics of Ketman in The Captive Mind (Zniewolony umysł). Finally, this paper presupposes that the theory of equilibrium of powers could be the issue of evil in the case of stagnation; therefore, the figures of the trickster, the action of triggering, and some level of a disequilibrium of powers are important for the human life as a condition of goodness.